Penerapan Metode Pemecahan Masalah (Problem Solving) untuk Meningkatkan Hasil Belajar IPS Siswa Sekolah Dasar - Wejang, Heronimus E.A.; Jamun, Yohannes Marryono; Ntelok, Zephisius R. E. (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The problems of this research are first, students in elementary school got the low learning outcomes for social studies and second, the learning process is still dominated by the monotonous lecture method. This study aims to determine the application of problem solving methods that can foster students' thinking, involve students to solve their own problems in the learning process, and generate confidence in students, especially in social studies lessons.The type of this research is literature review. The data used in this study were taken from the results of previous research on the application of problem solving methods to improve social studies learning outcomes for elementary students.Based on the results of the study, it was concluded that the application of problem solving methods in social studies learning could improve social studies learning outcomes for elementary students. Based on the conclusions above, it is recommended for prospective teachers to further examine the factors that cause students' low social studies learning outcomes. For teachers, they should motivate the students more in learning and getting to know more about the importance of applying problem solving methods to find out other factors that cause students' low social studies learning outcomes.